Martyrius, a Hieromonk of the Kievan Caves Monastery (the Fifteenth Century): Clarifying the Scope of His Works - Temčinas, Sergejus (Senoji Lietuvos literatūra, 2024)
The article is devoted to the hieromonk Martyrius, the little-known fifteenth-century Ruthenian hymnographer at the Kievan Caves Monastery, who is believed to have compiled a week cycle of translated Byzantine akathists with the addition of two compositions of his own. These activities are described in an anonymous manuscript text entitled ‘Последование о стихословии икосов’ (‘The Sequence on the Reciting Oikoi’, as akathists are referred to here in the Greek manner). Two akathists, dedicated, respectively, to All Saints (for Saturday) and John Chrysostom (for Sunday), are inscribed with his name in some manuscript copies. A prayer to John Chrysostom, accompanying Martyrius’s original akathist to this church father and containing the anonymous author’s request to the saint to accept the oikoi dedicated to him as a gift was also recently attributed to this writer. The article enumerates manuscript copies of the hymnographic and euchographic works attributed to Martyrius, whether definitely or allegedly, and argues for his authorship only in regard of the two akathists whose titles explicitly mention his name in manuscript sources. These became the earliest original compositions of this genre created in the Grand Duchy of Lithuania and, apparently, in Eastern Slavia in general. The article contains a publication of ‘The Sequence on the Reciting Oikoi’, probably compiled by a later anonymous author.